Superoxide Dismutase (SOD) Activity in Cryopreserved Semen of Itik Pinas-Khaki (Anas platyrhynchos L.) - A. E. Ancuelo; M. M. Landicho; G. A. Dichoso; P. Sangel (Faculty of Animal Science, Bogor Agricultural University, 2021)
Cryopreservation induces oxidative stress on sperm due to an increase in the number of reactive oxygen species (ROS), thereby resulting in decreased sperm quality. ROS's destructive potential is normally counteracted in sperm by their innate antioxidant system consisting of enzymes, which include superoxide dismutase (SOD). This study aimed to assess the quality of semen from Itik Pinas-Khaki (IP-Khaki) drakes that were cryopreserved with either 4.5% DMSO or 7.0% glycerol as cryoprotectant through evaluation of total sperm motility (%) and determination of SOD activity (U/mL). Here, semen samples were collected from 12 sexually mature IP-Khaki drakes, an improved egg-type breed of Philippine mallard duck, and processed using modified reported cryopreservation procedure for ducks. Results showed that post-thawing total sperm motility averages of 12.04±5.61% using 4.5% DMSO and 13.99±5.28% using 7.0% glycerol were comparable. Moreover, similar SOD activity levels of 0.39±0.18 U/mL with 4.5% DMSO and 0.33±0.21 U/mL with 7.0% glycerol in 2.00 x 108 IP- Khaki sperm cells were also observed. The observed very low intracellular SOD activity indicates severe damage to sperm cells due to cryopreservation, which resulted in a comparably low total sperm motility with either of the cryoprotectants. Thus, the cryopreservation protocol used is not the optimum for IP- Khaki semen based on the observed considerable decline in sperm motility and very low SOD activity after cryopreservation.